GLOBAL FREE MARKET COMPETITION OF ASEAN ECONOMIC COMMUNITY IN FACING DEMOGRAPHIC BONUS - Safitri, Selvina; Malik, Ihtisam Abdul (SYNTIFIC, 2023)
Background. For our country Indonesia, since the formation of the Creative Economy Agency (hereinafter referred to as BEKRAF), it turns out that the government has begun to see that the creative industry put together with the creative economy is an extraordinary potential for economic growth of the Indonesian state in the future. Research Purpose. This research aims to analyze the correlation between the creativity industry and the creativity economy. Research Method. This study employs a qualitative descriptive method. Data collection is carried out through unstructured interviews using purposive sampling. Findings. Related (1) correlates with the expansion of employment to overcome. Unemployment results in the demographic bonus of 2045, until the productive workforce is greater than the non-productive workforce (0-15 years + 65 years and over). Not to mention facing labor competition (outsourcing) between countries, both at the regional and international levels, and (2) equitable economic development for the community as well as overcoming various gaps in people's lives. Conclusion. The rise of the people's economy based on the creative industry and the creative economy in SMEs in Bali, opportunities and challenges in facing the global free market of the Asian Economic Community with the Asian Economic Community.